1994
DOI: 10.3928/0098-9134-19941101-06
|View full text |Cite
|
Sign up to set email alerts
|

The Terminally Ill: SERENITY NURSING INTERVENTIONS FOR HOSPICE CLIENTS

Abstract: 1. Serenity is an inner peace that is independent of external events. It often is desired by persons near death. 2. Information about nursing interventions to facilitate clients' serenity, however, is missing from the literature. 3. In the study presented, pain control, therapeutic touch, and assisting clients to build trust were the three highest-ranked interventions on both effectiveness and frequency of use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Qualitative studies have supported the spiritual nature of hope. [42][43][44] in her study of 45 individuals with cancer and 45 individuals with other chronic illnesses found that the most commonly supported sources of hope were family, friends, and religious beliefs. Wake and Miller's 33 multinational study of hope-inspiring strategies found that US nurses were the only respondents suggesting spiritual strategies as a means of fostering hope.…”
Section: Discussionmentioning
confidence: 96%
“…Qualitative studies have supported the spiritual nature of hope. [42][43][44] in her study of 45 individuals with cancer and 45 individuals with other chronic illnesses found that the most commonly supported sources of hope were family, friends, and religious beliefs. Wake and Miller's 33 multinational study of hope-inspiring strategies found that US nurses were the only respondents suggesting spiritual strategies as a means of fostering hope.…”
Section: Discussionmentioning
confidence: 96%
“…Roberts and colleagues have begun the seminal work with serenity by conducting a concept analysis, providing an instrument to measure serenity [3][4][5][13][14][15] and have studied aspects of serenity in helping older adults and hospice patients. 4,5 Following Parse's methods, [16][17][18] Kruse 19 studied the meaning of serenity for survivors of cancer. With the exception of a theoretical analysis of personal experience of how lesbian women recover from alcoholism, 20 no other research has addressed the experience of serenity in recovery from addiction, particularly from the perspective of unitary life patterns.…”
Section: Review Of Researchmentioning
confidence: 99%
“…Serenity has been defined as a desirable spiritual state of "sustained inner peace," 3 and "independent of external events," 3 that is thought to decrease stress and improve physical and emotional health. [3][4][5] For those whose lives have been shattered by addiction, serenity is experienced, perceived, and expressed as a regenerating, inspiriting, strengthening, healing change in life orientation in a journey toward recovery and wholeness.…”
mentioning
confidence: 99%
“…For hospice interventions targeting patients at the end of life, therapeutic touch has been found to be one of the highest ranked interventions in terms of effectiveness and frequency (Messenger & Roberts, 1994). As Sandelowski (2002) argues, physical encounters are especially dramatized in touch and remind both the health care provider and the patient that to know the patient means to have knowledge of the "particularity of the patient's body.…”
Section: Lack Of Human Touchmentioning
confidence: 99%